2012
DOI: 10.1002/bdm.1756
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Coherence and Inconsistency in Estimating Conditional Probabilities

Abstract: Two studies examined semantic coherence and internal inconsistency fallacies in conditional probability estimation. Problems reflected five distinct relationships between two sets: identical sets, mutually exclusive sets, subsets, overlapping sets, and independent sets (a special case of overlapping sets). Participants estimated P(A), P(B), P(A|B), and P(B|A). Inconsistency occurs when this constellation of estimates does not conform to Bayes' theorem. Semantic coherence occurs when this constellation of estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…8 Thus, interventions applying FTT (incorporated in BRCA Gist) have been successful in helping people make sense of such relations, reducing biases and improving decision making. 8,30,55,61,62 …”
Section: Fuzzy-trace Theorymentioning
confidence: 99%
“…8 Thus, interventions applying FTT (incorporated in BRCA Gist) have been successful in helping people make sense of such relations, reducing biases and improving decision making. 8,30,55,61,62 …”
Section: Fuzzy-trace Theorymentioning
confidence: 99%
“…For example, taking an individual differences approach, using the FPPI may shed light on Bayesian reasoning (Chater, Oaksford, Hahn, & Heit, 2010;Fisher & Wolfe, 2012) or even biases in reasoning and argumentation (Wolfe & Britt, 2008;Wolfe, Britt, & Butler, 2009). The FPPI can also be used in applied research, particularly in medical decision making (Peters, McCaul, Stefanek, & Nelson 2006;Reyna, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that in comparison to the control group, learning about Euler diagrams and 2 × 2 tables improved semantic coherence and decreased inconsistency, although understanding some set relations were helped more by particular representations. These findings demonstrated that clarifying appropriate denominators reduce errors by affecting class inclusion reasoning (Wolfe et al, in press). …”
Section: Human Factors In Risk Communicationmentioning
confidence: 95%
“…Because ratios involve classes that overlap (e.g., number of people with disease or number of people with a positive test result), confusion arises from identifying the denominator (e.g., number of people with disease overall or number of people with positive test result overall). According to this theory, risk communication strategies should focus on making the denominator clear (discretely) by disentangling the classes that overlap, which reduces errors (Wolfe, Fisher, and Reyna, in press; Reyna & Mills, 2007). …”
Section: Human Factors In Risk Communicationmentioning
confidence: 99%
See 1 more Smart Citation